Growth effects of systemic versus inhaled steroids in chronic lung disease. Issue 1 (1st July 2002) - Nicholl, R M; Greenough, A; King, M; Cheeseman, P; Gamsu, H R
Abstract : Aim: To compare the effects of inhaled and systemic steroids on growth in very low birthweight (VLBW) infants with chronic lung disease (CLD). Methods: Sixteen babies with CLD randomly received inhaled budesonide (100 μg four times daily for 10 days via Aerochamber) or systemic steroids (dexamethasone 0.5 mg/kg/day, reducing over nine days). Linear growth (lower leg length, LLL) was measured by knemometry twice weekly. Results: The gestational age, birth weight, postnatal age, and LLL velocity (LLLvel) were similar between the two groups at the start of treatment. At the end of the treatment period, LLLvel was reduced in the dexamethasone group (mean −0.01 mm/day) but had increased in the budesonide group (mean 0.48 mm/day). Mean weight gain was non-significantly lower in the dexamethasone group (5.8 g/kg/day) compared to the budesonide group (mean 12.7 g/kg/day). Conclusion: Inhaled budesonide has less short term effects on growth than systemically administered dexamethasone.